European media governance : national and regional dimensions. - Terzis, Georgios, ....- (Bristol : Intellect, 2007)
A multitude of factors affect how the European media industry is governed, including commercialisation, concentration, convergence and globalisation. George Terzis' collection, European Media Governance, is the first volume to concentrate on analysing and explaining how European countries are slowly conceding control of the media from the government to the market, professional and public forces. This impressive volume provides a detailed examination of all aspects of media governance, including media ownership structures, government policies, citizen's organisations and union's accountability systems, for 32 European countries. European Media Governance includes recent research into technological developments and provides sources for more information in each country. In addition to this incredibly diverse scale of research and analysis, the book provides a companion website with regular updates. Terzis' European Media Governance addresses all aspects of media governance in Europe, reflecting contemporary developments in both the countries analysed and their media, creating a comprehensive and reliable source.
Keywords: Media en maatschappij; Media en politiek; Media